IT Project Portfolio Selection using Analytic Hierarchy Process - Rivera Chávez, Arturo (2008)
Based on the concepts of decision support system (DSS), a framework is presented for IT portfolio selection, which could be adaptable in different degrees to the needs of the different stakeholders of the company. This framework provides a flexible, expandable and interactive DSS to select IT projects for portfolio management A case is showed to demonstrate the practical application of the proposed approach.